PENGARUH PENDAPATAN USAHA DAN BEBAN USAHA TERHADAP LABA BERSIH PADA PT. NIPPON INDOSARI CORPINDO TBK - Nurul Huda; Isti Mutmainnah (JUIMA : JURNAL ILMU MANAJEMEN, 2020)
This study aims to determine the effect of Operating Revenues and Operating Expenses on Net Profit at PT Nippon Indosari Corpindo Tbk. The population in this study is the income statement data for 10 years and the research sample for 9 years with the sampling used is purposive sampling. This research is an associative research, using a quantitative approach consisting of secondary data. The process of collecting research data uses the literature study and documentation method. To measure the effect of operating revenues and operating expenses on net income of PT Nippon Indosari Corpindo Tbk using multiple regression analysis through the F Test and t Test. The results of this study indicate that operating income has a partially significant effect on net income, operating expenses have no significant effect partially on net income. While operating revenues and operating expenses simultaneously have a significant effect on net income.